Soil Nutrient Dynamics of Mature Rubber (Hevea brasiliensis Muell. Arg.) Plantation in Relation to Phenology and Growing Environment - Vijayaraghavakumar, S. Meti, M. Meerabai, M. Abdul Salam J. Jacob and (Journal of the Indian Society of Soil Science, 2015)
Para rubber (Hevea brasiliensis Muell. Arg.) is grown on varied soil and climate condition in traditional rubber growing regions of India. Owing to its attractive profit, natural rubber (NR) is being grown beyond its ideal elevation of 300 m but poor performance at high elevation has been reported. Hence, a study was undertaken to understand the soil nutrient dynamics and phenology of mature rubber plantation at different elevation induced growing environment in Kottayam district of Kerala. Climate, particularly maximum (Tmax) and minimum (Tmin) temperature, rate of litter decomposition, nitrogen (N) mineralization potential, dynamics of soil organic carbon (SOC), total N and exchangeable aluminium (Al) showed significant variation along the elevation gradient. Litter decomposition rate, N mineralization potential were low at high elevation resulting in longer SOC turnover period and hence significant increase in SOC content with increase in elevation was noticed. Dynamics of soil total N showed peak for short period at high elevation compared to low elevation. Number of new flushes were less and annual leaf shedding was early at high elevation indicating the shortened growing period compared to low elevation. Rubber tree at high elevation showed significantly higher nutrient resorption for P and K indicating the limited availability of these nutrients. Factor analysis extracted mineralization and climate factors at high elevation and only climate factor showed significant positive correlation with next month rubber yield indicating the importance of climate factor in rubber ecosystem at high elevation. At low elevation extracted climate component did not show significant correlation with rubber yield, indicating climate condition at low elevation is not limiting rubber performance. Present study showed the use of elevation gradient as a potential natural resource for studying climate effect on nutrient dynamics, plant phenology and performance.